Associations between artificial light at night and risk for thyroid cancer: A large US cohort study. Issue 9 (8th February 2021) - Zhang, Dong; Jones, Rena R.; James, Peter; Kitahara, Cari M.; Xiao, Qian
Abstract : Background: Light at night (LAN) inhibits nighttime secretion of melatonin and may cause circadian disruption, which may be a risk factor for cancer. Recent studies have linked high LAN exposure with elevated breast cancer risk. Given that breast cancer may share a common hormone‐dependent etiology with thyroid cancer and that circadian rhythms play a role in regulating thyroid function, the authors hypothesized that exposure to LAN is positively associated with thyroid cancer incidence. Methods: This study examined the association between LAN and thyroid cancer incidence in the National Institutes of Health–American Association of Retired Persons Diet and Health Study. LAN exposure was estimated from satellite data and was linked to residential addresses at the baseline. Incident thyroid cancer cases were ascertained via linkage to state cancer registries. Cox regression was used to determine the relationship between LAN and thyroid cancer risk, with adjustments made for sociodemographic, lifestyle, and other environmental factors. Results: Among 464, 371 participants, a positive association was found between LAN and thyroid cancer risk. Specifically, in comparison with the lowest quintile of LAN, the highest quintile was associated with a 55% increase in risk (hazard ratio [HR], 1.55; 95% confidence interval [CI], 1.18‐2.02). The association was primarily driven by papillary thyroid cancer and was stronger in women (HR, 1.81; 95% CI, 1.26‐2.60) than men (HR, 1.29; 95% CI, 0.86‐1.94). In women, the association was stronger for localized cancer, whereas in men, the association was stronger for a more advanced stage. Results were consistent across different tumor sizes. Conclusions: LAN was positively associated with thyroid cancer risk. Future studies are needed to confirm this association and identify underlying biological mechanisms. Abstract : This study reports that higher exposure to light at night is associated with a higher risk for thyroid cancer. The association is stronger for women than men, and this cannot be fully explained by a detection bias.